2015
DOI: 10.1016/j.paid.2014.08.041
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anthropomorphic tendencies on human hoarding behaviours

Abstract: a b s t r a c tHoarding is the excessive acquisition of and failure to discard possessions. Previous research has shown a link between anthropomorphism (the tendency to ascribe human characteristics to non-human objects) and hoarding. Here we assess the psychometric properties of a new Anthropomorphism Questionnaire (AQ) in a nonclinical sample of 264 adults. A further sample of 93 participants was then recruited to assess relationships between hoarding behaviours and cognitions, scores on the AQ, an existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 24 publications
7
75
2
1
Order By: Relevance
“…Both subscales have demonstrated high internal consistency (childhood items, α=.91; general items, α=.86) (Neave et al, 2015). In our sample α=.93 for the total score.…”
Section: Methodsmentioning
confidence: 52%
See 3 more Smart Citations
“…Both subscales have demonstrated high internal consistency (childhood items, α=.91; general items, α=.86) (Neave et al, 2015). In our sample α=.93 for the total score.…”
Section: Methodsmentioning
confidence: 52%
“…Timpano and Shaw (2013) revealed that anthropomorphic tendencies were significantly associated with greater hoarding symptoms, with anthropomorphic tendency scores most strongly associated with emotional attachment, as a measure of hoarding cognitions. Neave, Jackson, Saxton & Hönekopp (2015) also demonstrated that anthropomorphising was a significant predictor of hoarding behaviours in a non-clinical sample.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…As pessoas podem apresentar menor disposição para substituir um produto quando levam em consideração aspectos antropomórficos (CHANDLER; SCHWARZ, 2010). E, em algumas pessoas, podemos observar até comportamentos compulsivos de consumo relacionados a antropomorfização, como por exemplo o comportamento de acumulação (TIMPANO;SHAW, 2013;NEAVE et al, 2015).…”
Section: Conceito De Antropomorfizaçãounclassified